Forecasting Zakat Potential in BAZNAZ East Java Using the ARIMAX Method with Calendar Variation Effects - Sari, Lia Puspita; Hamid, Abdulloh; Khaulasari, Hani (Universitas Negeri Gorontalo, 2025)
Zakat is a Muslim act of worship that is related to wealth and is one of the instruments used in economic development so that it can solve the problem of poverty. According to the Central Statistics AgencyZakat is an Islamic obligation related to wealth distribution and functions as a key instrument in economic development, particularly in alleviating poverty. According to the Central Statistics Agency, East Java had the highest number of poor people in Indonesia in 2023. BAZNAS (Badan Amil Zakat Nasional) plays a strategic role in managing zakat funds to support poverty reduction efforts. Accurate information on zakat potential is crucial for ensuring the effective management and distribution of zakat. This study aims to model, evaluate the accuracy, and forecast the zakat potential at BAZNAS East Java untuk Januari sampai dengan Desember 2024 using the Autoregressive Integrated Moving Average with Exogenous (ARIMAX) Variables method. ARIMAX extends the ARIMA model by incorporating exogenous variables. In this study, the exogenous variables used are a deterministic trend and a Hijri calendar dummy variable representing the month of Ramadan, The results show that the best-performing model is ARIMAX([12],1,1), with a MAPE value of 18%, indicating a reasonably accurate forecast. The zakat potential for the next 12 months is projected to remain relatively stable, with a significant increase of IDR 6,674,988,827.25 expected in April 2024. This spike coincides with the month of Ramadan, when Muslims customarily pay zakat fitrah and zakat mal.